2014
DOI: 10.1186/2045-9912-4-16
|View full text |Cite
|
Sign up to set email alerts
|

Supplemental oxygen delivery to suspected stroke patients in pre hospital and emergency department settings

Abstract: BackgroundRecent data suggests that high-flow oxygen started promptly after stroke symptom onset salvages ischemic brain tissue. We investigated the consistency of oxygen delivery to suspected stroke patients in the pre-hospital (PH) and Emergency Department (ED) settings, and associated adverse events (AEs).MethodsWe retrospectively reviewed pre-hospital call reports of suspected stroke patients transported by our institution’s paramedics. We extracted data on oxygen delivery in the PH and ED settings, demogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…The patients were categorized based on the amount of oxygen administered in the ED: none, low-flow (2-4 L/min), and high-flow (10-15 L/min). In comparison with the low-flow and no-oxygen groups, the highflow group had a lower occurrence of adverse events (defined as death rate, neurological deterioration status, or occurrence of ischemic event) [57]. Thus, neither of the retrospective studies reported any neurologic harm associated with oxygen administration.…”
Section: • Pharmacological Interventionsmentioning
confidence: 84%
See 1 more Smart Citation
“…The patients were categorized based on the amount of oxygen administered in the ED: none, low-flow (2-4 L/min), and high-flow (10-15 L/min). In comparison with the low-flow and no-oxygen groups, the highflow group had a lower occurrence of adverse events (defined as death rate, neurological deterioration status, or occurrence of ischemic event) [57]. Thus, neither of the retrospective studies reported any neurologic harm associated with oxygen administration.…”
Section: • Pharmacological Interventionsmentioning
confidence: 84%
“…It was demonstrated that neurological outcomes (defined as mRS and ambulatory status) did not differ among the three groups (hyperoxia, hypoxia and normoxia) [56]. Additionally, a retrospective analysis examined the reliability of oxygen administration to suspected stroke subjects in the ED and out-of-hospital setting and explored adverse events among these patients [57]. The patients were categorized based on the amount of oxygen administered in the ED: none, low-flow (2-4 L/min), and high-flow (10-15 L/min).…”
Section: • Pharmacological Interventionsmentioning
confidence: 99%
“…The frequency of adverse events was lower in the high-flow oxygen group. Adverse events and oxygen treatment were found to be associated with diagnoses of intracerebral hemorrhage, encephalopathy, and seizure but not with amount of oxygen delivered [40]. Thus, neither Dylla et al nor Chan et al found oxygen treatment to be associated with neurologic harm and both found disease severity and final diagnosis to be drivers of oxygen treatment.…”
Section: Hyperoxia During Ems Transportmentioning
confidence: 94%
“…Supplemental oxygen can be administered at a dose of 10-15 L/min if there is evidence of hypoxia by pulse oximetry. This was shown to slow down the process of ischaemia and extend the therapeutic time window for thrombolysis [20,21]. Patients with depressed level of consciousness should be intubated to avoid the risk of aspiration [22].…”
Section: Airway Managementmentioning
confidence: 99%